Neonatal Surgical Morbidity and Mortality at a Single Tertiary Center in a Low- and Middle-Income Country: A Retrospective Study of Clinical Outcomes - Hasan, Md Samiul; Islam, Nazmul; Mitul, Ashrarur Rahman (Frontiers in Surgery, 2022)
Background The most challenging and demanding issue in Pediatrics and Pediatric Surgery is to deal with neonatal surgery which almost always involves emergency neonatal surgical conditions. Emergency neonatal surgery most often involves congenital anomalies. More than 90% of these anomalies occur in low- and middle-income countries (LMICs) like Bangladesh. This considerable load of patients and inadequate resources in their management continue to be an unconquerable challenge for pediatric and neonatal surgeons in this region. We aim to review the challenges and constraints influencing the outcomes of emergency neonatal surgery which will guide to propose expectations from the global community. Method We reviewed hospital records of neonates admitted to a tertiary care pediatric hospital between January 2016 and December 2020. Demographic and clinical data were extracted using a questionnaire and analyzed using SPSS 25. Results A total of 3,447 neonates were admitted during the five-year study period. More than 80% of the patients had at least one prenatal ultrasonography (USG) scan, but less than 10% had a prenatal diagnosis. More than 70% of the anomalies of the patient involved the gastrointestinal tract and abdominal wall. Overall mortality was an alarming 14.6%. Gastroschisis (>90%) and esophageal atresia (>85%) mainly contributed to this high mortality. The challenges detected in this review were the absence of a prenatal diagnosis, limited access to intensive care facilities, unavailability of parenteral nutrition, inadequate monitoring, and hospital-acquired sepsis. Conclusion Emergency neonatal surgery contributes to a significant proportion of neonatal mortality. A holistic approach is essential to improve the situation, including the infrastructure and human resource development, identification of causes, and implementation of preventive measures to reduce the patient load. Global collaboration remains to be a vital factor to mitigate these multifactorial constraints.